The Effect of Holding Pressure and Inject Pressure to Short Shot Defect in Injection Molding Cover Pot: Pengaruh Holding Pressure dan Inject Pressure Terhadap Short Shot Defect pada Proses Injection Molding Cover Pot - Muhammad Sambodo Aribowo; Agus Dani (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
The influence of inappropriate injection molding parameters often results in product defects, one of which is the short shot, which is a condition where the plastic to be injected into the cavity does’t reach the ideal capacity. The purpose of this research is to understand and be able to explain the parameters of holding pressure, inject pressure, and the interaction of these two parameters on short shot defects in cover pot products with the injection molding process. This research uses independent variables, namely holding pressure with variations of 20 Bar, 30 Bar, and 40 Bar and inject pressure with variations of 15 Bar, 30 Bar, and 45 Bar and dependent variables in the form of short shot defects. The method used in this research is a factorial experiment with replication of 10 (ten) times and data processing analysis using ANOVA with the help of Minitab 21.2.0 statistical software. The result of this research is that there is a significant influence of holding pressure, inject pressure, and the interaction of these two parameters on short shot defects in cover pot products with injection molding process. The average weight of the product produced at the interaction of the parameters holding pressure 40 Bar and inject pressure 45 Bar is 8.8 grams (normal) so as to minimize product defects to improve the quality and quantity of cosmetic packaging production cover pot.